OP0177 Ultrasound in The Management of Rheumatoid Arthritis: Results from The Randomized Controlled Arctic Trial. (15th July 2016) - Haavardsholm, E.A.; Aga, A.-B.; Olsen, I.C.; Lillegraven, S.; Hammer, H.B.; Uhlig, T.; Fremstad, H.; Madland, T.M.; Lexberg, Å.S.; Haukeland, H.; Rødevand, E.; Høili, C.; et al.
Abstract : Background: Application of ultrasound (US) in the management of patients with rheumatoid arthritis (RA) is rapidly growing. Objectives: The randomized controlled ARCTIC trial (ClinicalTrials.gov NCT01205854 ) examined if the use of a treatment strategy based on structured US assessment 1 would lead to improved outcomes in RA, compared to a conventional strategy based on clinical and laboratory assessments alone. Methods: Newly diagnosed DMARD naïve RA patients were randomized 1:1 to A) an ultrasound tight control (UTC) strategy targeting clinical and imaging remission (no ultrasound power-Doppler signal) or B) a conventional tight control (CTC) strategy targeting clinical remission. Patients in both arms were treated according to the same DMARD escalation strategy, starting with MTX, then triple therapy MTX/SSZ/HCQ, then biologic DMARD if target was not reached. The primary endpoint was the proportion of patients with a combination between 16 and 24 months of clinical remission, no swollen joints and non-progression of radiographic joint damage. Results: A total of 238 patients were randomized, and patients with at least one follow-up visit were included in the full analysis set (UTC n=118, CTC n=112). Twenty-six patients (22.0%) in the UTC arm and 21 patients (18.8%) in the CTC arm reached the primary endpoint (mean difference 3.3%; 95%CI -7.1% to 13.7%). No significant differences were found between the groups for the components of the primary outcome, and secondary endpoints were similar (table). Conclusions: The implementation and systematic use of ultrasound in the follow-up of early RA patients treated with an aggressive treat-to-target strategy is not justified based on the results of the ARCTIC trial. References: Hammer HB et al Ann Rheum Dis 2011 Disclosure of Interest: E. Haavardsholm Grant/research support from: Pfizer, MSD, UCB, AbbVie, Roche, A.-B. Aga: None declared, I. Olsen: None declared, S. Lillegraven: None declared, H. Hammer Consultant for: AbbVie, Pfizer, BMS, Roche, UCB, T. Uhlig: None declared, H. Fremstad: None declared, T. Madland: None declared, Å. Lexberg: None declared, H. Haukeland Consultant for: UCB, AbbVie, E. Rødevand: None declared, C. Høili: None declared, H. Stray: None declared, A. Bendvold: None declared, I. Hansen: None declared, G. Bakland Consultant for: AbbVie, Pfizer, L. Nordberg: None declared, D. Heijde: None declared, T. Kvien: None declared